Urgensi Pengaturan Lame Duck Session (Sesi Bebek Lumpuh) dalam Lembaga Dewan Perwakilan Rakyat Republik Indonesia - Nuryadin, Nuryadin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
During the transition of power, a phenomenon known as the lame duck session occurred, in which an official whose term of office was about to expire, and his successor had been elected. The change of leadership from an active official to a new official who has been elected based on the election results, basically creates a time gap between the day of determining the election results and the day of the inauguration of the elected officials. Problems that then arise as a result of this are the policies taken by officials who are still active at the end of their term of office, and legal uncertainty in making policies that benefit certain parties. Based on the comparisons made, the lame duck session arrangement contained in the constitutions of other countries is in the form of tightening the election schedule and the appointment of members of parliament, which is aligned with the period of the parliamentary session. The shorter the schedule, the shorter the duration of the parliamentary lame duck session. In Indonesia, setting limits on the holding of general elections, the appointment of elected members of parliament and the schedule for holding the session period need to be contained in the constitution of the Republic of Indonesia. Considering that this arrangement is political in nature, if it is only stated in legislation, it will be easy for the House of Representatives to make changes in accordance with the interests of the majority of members of parliament.Keywords: lame duck session, Indonesia AbstrakPada masa transisi kekuasaan, terjadi sebuah fenomena yang dinamakan sebagai lame duck session, di mana pejabat yang masa jabatannya akan segera berakhir, dan penggantinya telah terpilih. Pergantian kepemimpinan dari pejabat yang masih aktif ke pejabat baru yang telah terpilih berdasarkan hasil pemilu, pada dasarnya menimbulkan sebuah celah waktu antara hari penetapan hasil pemilu dan hari pelantikan pejabat terpilih. Permasalahan yang kemudian muncul akibat hal tersebut adalah terhadap kebijakan-kebijakan yang diambil oleh pejabat yang masih aktif diakhir masa jabatannya, dan ketidakpastian hukum dalam pengambilan kebijakan yang menguntungkan pihak-pihak tertentu. Berdasarkan perbandingan yang dilakukan, pengaturan lame duck session yang dimuat dalam konstitusi negara-negara lain berupa pengetatan jadwal pemilu dan pengangkatan anggota parlemen, yang diselaraskan dengan masa persidangan parlemen. Semakin singkat jadwalnya, maka durasi lame duck session parlemen menjadi lebih singkat pula. Di Indonesia pengaturan batas penyelenggaraan pemilihan umum, pengangkatan anggota parlemen terpilih dan jadwal penyelenggaraan masa sidang perlu dimuat dalam konstitusi Republik Indonesia. Mengingat pengaturan ini bersifat politis, jika hanya dituangkan dalam peraturan perundang-undangan, maka Dewan Perwakilan Rakyat akan mudah untuk melakukan perubahan sesuai dengan kepentingan mayoritas anggota parlemen.Kata kunci: Periode Bebek Lumpuh; Lame Duck Session; Indonesia